Synthesis and biological assessment of racemic benzochromenopyrimidinetriones as promising agents for Alzheimer's disease therapy. (May 2017) - Dgachi, Youssef; Martin, Helène; Bonet, Alexandre; Chioua, Mourad; Iriepa, Isabel; Moraleda, Ignacio; Chabchoub, Fakher; Marco-Contelles, José; Ismaili, Lhassane
Aim: Due to the complex nature of Alzheimer's disease, there is a renewed search for multitarget directed drugs.Results: This paper describes the synthesis and in vitro biological evaluation of six racemic 13-aryl-2, 3, 4, 13-tetrahydro-1 H, 12 H -benzo[6, 7]chromeno[2, 3-d]pyrido[1, 2- a ]pyrimidine-7, 12, 14-triones (1a–6a ), and six racemic 15-aryl-8, 9, 10, 11, 12, 15-hexahydro-14 H -benzo[6′, 7′]chromeno[2′, 3:4, 5] pyr-imido [1, 2- a ]azepine-5, 14, 16-triones (1b–6b ), showing antioxidant and cholinesterase inhibitory capacity. Among these compounds, 13-phenyl-2, 3, 4, 13-tetrahydro-1 H, 12 H -benzo[6, 7]chromeno[2, 3- d ]pyrido[1, 2- a ]pyrimidine-7, 12, 14-trione(1a) is a nonhepatotoxic at 300 μmol/l dose concentration, and a selective Ee AChE inhibitor showing good antioxidant power.Conclusion: A new family of racemic benzochromenopyrimidinetriones has been investigated for their potential use in the treatment of Alzheimer's disease.